Development and characterization of 11 polymorphic microsatellite markers in Tapiscia sinensis (Staphyleaceae)1. (9th December 2013) - Zhang, Pengfei; Wang, Zhiguang; Liu, Yaling; Tian, Hua; Yao, Xiaohong; Zhang, Jinju
Abstract : Premise of the study: We developed and characterized five polymorphic microsatellite loci from an AC‐enriched genomic library of a rare tree, Tapiscia sinensis, and six compound microsatellite primers using a dual‐suppression‐PCR–based approach, to investigate geographical genetic structure. Methods and Results: The polymorphism of these loci was assessed in 102 samples collected from three populations. The number of alleles per locus ranged from one to nine. Expected heterozygosity per locus ranged from 0.000 to 0.709 and observed heterozygosity ranged from 0.000 to 0.750. Five loci deviated from Hardy–Weinberg equilibrium after Bonferroni correction. Conclusions: This set of microsatellites may be useful for investigating broad‐scale genetic variation in the extant populations of the endangered tree species T. sinensis .